2018
DOI: 10.1126/sciadv.aao1167
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating rates of Arctic carbon cycling revealed by long-term atmospheric CO 2 measurements

Abstract: Atmospheric CO2 observations reveal a decrease in Arctic ecosystem carbon residence time over the past four decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 44 publications
(75 reference statements)
5
79
0
Order By: Relevance
“…Similar to a previous analysis (Commane et al, ; Jeong et al, ), we also found warming significantly increased cold season respiration during the 2015/2016 El Niño year, which offset carbon uptake enhancement from earlier growing season onset and warmer temperatures during the subsequent spring within the ABoVE domain. If a faster rate of cold season warming unfolds as predicted, the magnitude and duration of cold season respiration carbon loss will be greatly enhanced (Natali et al, ; Webb et al, ; Zona et al, ), and potentially switch high‐latitude ecosystems from a net carbon sink to a carbon source, thereby reinforcing a positive carbon–climate feedback in the Earth system (Huang et al, ; Koven et al, ; Schaefer, Lantuit, Romanovsky, Schuur, & Witt, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to a previous analysis (Commane et al, ; Jeong et al, ), we also found warming significantly increased cold season respiration during the 2015/2016 El Niño year, which offset carbon uptake enhancement from earlier growing season onset and warmer temperatures during the subsequent spring within the ABoVE domain. If a faster rate of cold season warming unfolds as predicted, the magnitude and duration of cold season respiration carbon loss will be greatly enhanced (Natali et al, ; Webb et al, ; Zona et al, ), and potentially switch high‐latitude ecosystems from a net carbon sink to a carbon source, thereby reinforcing a positive carbon–climate feedback in the Earth system (Huang et al, ; Koven et al, ; Schaefer, Lantuit, Romanovsky, Schuur, & Witt, ).…”
Section: Discussionsupporting
confidence: 91%
“…Climate warming has lengthened the growing season and contributed to high‐latitude greening that has greatly enhanced photosynthetic carbon dioxide (CO 2 ) uptake in the Northern Hemisphere over the past five decades (Ciais et al, ). However, high‐latitude ecosystem warming also has the potential to enhance the decomposition of vast quantities of soil organic matter stored in permafrost soils, increasing soil carbon losses to the atmosphere, and reinforcing further climate warming (Commane et al, ; Jeong et al, ; Piao et al, ). The timing and magnitude of these photosynthetic and respiration responses to climate change have the potential to alter ecosystem carbon dynamics, and the magnitude and seasonality of atmospheric CO 2 concentrations (Anderegg et al, ; Graven et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Commane et al. ; Jeong et al., ). An increase in carbon storage in the maritime forest region of Alaska during recent decades has been estimated using forest inventory data from the region (U.S. Department of Agriculture Forest Service ).…”
Section: Discussionmentioning
confidence: 99%
“…, Commane et al. ; Jeong et al., ). Fire disturbance has also been identified as an important factor that can affect carbon balance of tundra (Mack et al.…”
Section: Introductionmentioning
confidence: 99%